Adaptive Strategy of Woody Trees and Shrubs of Tamaulipan Thorn Scrub in Xeric Environments - Maiti, Ratikanta; Rodriguez, Humberto Gonzalez; Kumari, Aruna (International Journal of Bio-resource and Stress Management, 2016)
Woody trees and shrubs in Tamaulipan Thorn Scrub in Northeastern Mexico are exposed to hot summer with temperature rising to 45 °C. These woody species adopt different morpho-anatomical and ecophysiological mechanism for adaptation to these xeric environments. Among these tree top crown, branching pattern, branching density help in the capture of solar radiation for photosynthesis, thereby reducing high temperature. Apart from these few anatomical traits such low or absence of stomata on adaxial surface and sunken stomata mainly on the abaxial surface prevent loss of transpiration, thereby maintaining water budget. In addition cuticular thickness, long and compact palisade cells help in better photosynthetic capacity as well as in reducing transpiration. Besides, the large variability in few ecophysiological traits such as pigments, epicuticular wax, macro-and micronutrients, and carbon sequestration (carbon fixation) help in the adaptation of woody species to xeric environments. It is recommended that the plantation of woody tree species with high carbon sequestration could reduce carbon from the atmosphere during capture of solar radiation and photosynthesis, thereby reducing high temperature and carbondioxide load in the atmosphere.